Robert B. Parker's Buried secrets [large type] - Parker, Robert B. (Parker, Robert B., 1932-2010. Jesse Stone novels, 2025)
"Chief of Police Jesse Stone is on his way home from a shift when a call comes in for a welfare check on an elderly resident. Inside a house packed with trash is a man's dead body. It's a sad, lonely end, but nothing criminal . . . until Jesse finds the photos of murder victims strewn around the corpse, on top of a treasure trove of $2 million in cash. Before long, Jesse has a price on his head, but the real danger might be coming from inside his own department. Jesse must unearth the truth buried under the wreckage of a dead man's life . . . before he winds up in the ground himself"--